TURNING PAGES, SHAPING MINDS: THE IMPACT OF LITERATURE ON ADOLESCENT DEVELOPMENT: TURNING PAGES, SHAPING MINDS: THE IMPACT OF LITERATURE ON ADOLESCENT DEVELOPMENT - Boymirzayeva, Dilnozahon (Журнал иностранных языков и лингвистики, 2025)
Adolescence is a crucial developmental period characterized by profound changes in social, emotional, and mental processes. Literature, especially fiction, has long been believed to contribute significantly to these shifts by providing readers with fresh viewpoints, poignant experiences, and creative settings for introspection. This study looks at the various ways that literature affects teenage development, with a special emphasis on thinking about others, empathy development, and building an identity. Literature plays a crucial role in forming the brains and hearts of teenagers, according to a meta-analysis of multidisciplinary research from the fields of psychology, education, and literary studies. There is a discussion on the implications of curriculum development and educational policies